Trapezoidal neutrosophic aggregation operators and their application to the multi-attribute decision-making process - Jana, C; Pal, M; Karaaslan, F; Wang, J Q (Scientia Iranica. Transaction E, Industrial engineering, 2020)
The aim of this paper is to introduce an interval trapezoidal neutrosophic set, which is a combination of trapezoidal fuzzy numbers, and an interval neutrosophic set. This paper presents some operational rules and the score and accuracy functions of interval trapezoidal neutrosophic numbers. Then, some aggregation operators based on interval trapezoidal neutrosophic information are proposed: the Interval Trapezoidal Neutrosophic Number Weighted Arithmetic Averaging (ITNNWAA) operator and the Interval Trapezoidal Neutrosophic Number Weighted Geometric Averaging (ITNNWGA) operator; in addition, the properties of these operators are investigated in detail. Furthermore, a multi-attribute decision-making method is developed based on the operators. Finally, a numerical example is presented to illustrate the applicability and effectiveness of the proposed method.